NSDLib: A comprehensive python library for network source detection and evaluation - Damian Frąszczak; Edyta Frąszczak (SoftwareX)
NSDLib, short for Network Source Detection Library, is an advanced package designed to detect the sources of propagation in networks. It is easy to integrate and offers a range of algorithms for source detection, including evaluating node importance, identifying outbreaks, and reconstructing propagation graphs. This library serves as a comprehensive repository, promoting collaboration among researchers and developers worldwide to combat disinformation warfare. By enabling the implementation and comparison of new techniques, NSDLib aims to enhance the understanding and mitigation of misinformation and improve propagation analysis. This paper provides an overview of NSDLib's capabilities, emphasizing its role in bridging the gap between theoretical research and practical application.